2019
DOI: 10.1111/nan.12571
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box M1 (FOXM1) transcription factor is a key oncogenic driver of aggressive human meningioma progression

Abstract: 2020) Neuropathology and Applied Neurobiology 46, 125-141 Forkhead box M1 (FOXM1) transcription factor is a key oncogenic driver of aggressive human meningioma progression Aims: Aggressive meningioma remains incurable with neither chemo-nor targeted therapies proven effective, largely due to unidentified genetic alterations and/or aberrant oncogenic pathways driving the disease progression. In this study, we examined the expression and function of Forkhead box M1 (FOXM1) transcription factor during meningioma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 55 publications
(75 reference statements)
5
27
0
2
Order By: Relevance
“…BIRC5 also promotes cell proliferation and invasion and inhibits apoptosis and cycle arrest (Su, 2016), and the aberrant methylation of BIRC5 was consistent basically with the previous report, which was identified by bioinformatics analysis (Cai et al, 2019). FOXM1 contributes to multiple cancers by promoting cellular proliferation and tumor initiation via β-catenin and cyclin D1 (Kim et al, 2019;Shukla et al, 2019). Bioinformatics analysis showed that FOXM1 was also involved in the development of hepatitis B virus (HBV)-related HCC (Xie et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…BIRC5 also promotes cell proliferation and invasion and inhibits apoptosis and cycle arrest (Su, 2016), and the aberrant methylation of BIRC5 was consistent basically with the previous report, which was identified by bioinformatics analysis (Cai et al, 2019). FOXM1 contributes to multiple cancers by promoting cellular proliferation and tumor initiation via β-catenin and cyclin D1 (Kim et al, 2019;Shukla et al, 2019). Bioinformatics analysis showed that FOXM1 was also involved in the development of hepatitis B virus (HBV)-related HCC (Xie et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Knockdown of FOXM1 in malignant meningioma cells led to decreased cell proliferation, angiogenesis and invasion by regulating cyclin D1 and p21. 27 While our Western blot results exhibited that siCCNB1 expedited the p53 pathway, while further oe-FOXM1 or CTPB contributed to the p53 pathway deficit.…”
Section: Dovepressmentioning
confidence: 61%
“…However, the increase in Wnts expressions induced by overexpression of FoxM1 in cultured renal tubular epithelial cells were not completely match what observed in UUO kidneys, which suggested that other factors other than FoxM1 might be involved in regulating Wnts expression. Moreover, FoxM1 was able to regulate β‐catenin transcription 27,28 and facilitate β‐catenin nuclear translocation 29‐31 . These studies indicated that the effect of FoxM1 in promoting renal fibrosis may not completely rely on regulating Wnts expressions.…”
Section: Discussionmentioning
confidence: 91%